PENGARUH DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR PAJAK PRATAMA MANADO - Djiko, Ivan Maikhel; Areros, William Agustinus; Kaparang, Sonny (Sam Ratulangi University, 2017)
This study aimed to determine the effect of labor discipline on the performance of employees at the Tax Office Pratama Manado. The method in this research using quantitative methods by means of correlation and regression analysis. From the results of research conducted work discipline is of significant importance to the values used in improving the performance of employees at the Tax Office Pratama Manado. Labor discipline and performance of employees showed significant differences, so that the otherwise positive relationship exists between the discipline of work with employee performance. Under the first hypothesis test of discipline working relationship with the employee's performance has a significant direction and shape of linear regression. Role in improving the performance of employees across differing greatly to the success of the performance of employees in the company or organization. To achieve a good performance of employees one of which will be obtained from labor discipline applied in any company or organization.Keywords: Discipline Work and Employee Performance